Treatment of U92+-U91+ collisions in spherical co-ordinates: going beyond the monopole approximation - McConnell, Sean R.; Artemyev, Anton; Surzhykov, Andrey (Physica scripta, 2013)
Recently, a new approach has been developed to treat the time-dependent two-centre Dirac equation within our group. This method generates basis wavefunctions describing an electron in the field of two nuclei at fixed internuclear distances in spherical co-ordinates, and uses coupled-channel techniques in handling the time dependences. Using this method, we analyse the electronic properties accompanying a U92+-U91+ collision for a zero-impact parameter. Specifically, the ground state occupation probability and the ionization probability has been calculated. Based on our calculations, we show the importance of using higher multipole terms in the expansion of the two-centre potential.
Im Titel sind "92+" und "91+" hochgestellt
Gesehen am 08.07.2021